Analysis of the Role of Compensation as a Moderator Variable in the Relationship Between Job Security and Turnover Intention in Restaurants Holding Company - Umi Setyorini; Lasrida Sigalingging; Darwin Kesuma; Fatimah Malini Lubis; Abdurohim (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
With compensation serving as a moderating variable, this study seeks to understand the relationship between job security and employees' intention to leave at one the company that focus on managing restaurants. 50 employees were used in the purposive sampling technique to determine the study's sample. Path analysis was used in this study's data analysis process, which was supported by the SPSS 26. The findings indicated that job security influences inclination to leave, the likelihood of turnover influences pay. According to the results of the Sobel test, reward is a mediating variable but is unable to mediate the relationship between and influence of job security characteristics on variables relating to turnover intention.